2007
DOI: 10.2134/agronj2006.0364
|View full text |Cite
|
Sign up to set email alerts
|

Crop Productivity and Economics during the Transition to Alternative Cropping Systems

Abstract: Many environmental benefits accrue from reducing tillage and increasing crop diversity; however, economic factors often encourage the continued use of intensive tillage and specialized crop production. This study examined crop yields, input costs, and economic returns during the transition to a range of cropping system alternatives in the northern Corn Belt region, including different system (organic, conventional), tillage (conventional, strip-tillage), rotation (corn-soybean, corn-soybean-wheat/alfalfa-alfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
99
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(115 citation statements)
references
References 29 publications
13
99
3
Order By: Relevance
“…Yields of grain crops are often, though not always, lower in organic than in conventional systems (Porter et al 2003;Delate and Cambardella 2004;Archer et al 2007;Cavigelli et al 2008). Nitrogen limitations are often an important factor limiting corn grain yield in organic systems (Berry et al 2002;Cavigelli et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Yields of grain crops are often, though not always, lower in organic than in conventional systems (Porter et al 2003;Delate and Cambardella 2004;Archer et al 2007;Cavigelli et al 2008). Nitrogen limitations are often an important factor limiting corn grain yield in organic systems (Berry et al 2002;Cavigelli et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In 2005, more than 55% of the organic field crop production hectares in Missouri were soybean, while Missouri ranked 23rd in the USA for the number of certified organic producers in 2007 [1]. Missouri farmers have noted increased profit margins with organic versus conventional crop production systems in mid-west states [2,3] and are more likely to consider using land previously set aside in the conservation reserve program for organic crop production [4]. Claypan soils in Missouri enrolled in the conservation reserve program generally are highly erodible.…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the mechanism, transition from industrial may be difficult if yields drop without price premiums on products or subsidies from governmental/non-governmental agencies to compensate for the loss [23,39,[87][88][89][90]. For example, in a global meta-analysis [39] found that farmers transitioning to conservation agriculture experienced a yield loss of around 3% for the first two years.…”
Section: Transitioning From Industrialmentioning
confidence: 99%
“…For example, in a global meta-analysis [39] found that farmers transitioning to conservation agriculture experienced a yield loss of around 3% for the first two years. Similarly, transitioning organic farmers may experience yield losses, and thus the usual three-year period before price premiums are realized through organic certification is financially difficult for farmers [23,[87][88][89][90]. The effect of the transition to organic on yields, however, is variable [45].…”
Section: Transitioning From Industrialmentioning
confidence: 99%
See 1 more Smart Citation